(untitled) (Progressive Agriculture, 2014)
The study was conducted to produce fish sauce from small freshwater fishes like Kholisa (Colisa fasciatus), Tit punti (Puntius ticto), Jat punti (Puntius sophore), Tengra (Mystus vittatus), Taki (Channa punctatus), Gutum (Lepidocephalichthys guntea), Guchi (Macrognathus pancalus), Veda (Nandus nandus), and Bujuri (Mystus tengara) by using different concentrations of salt (25% as Treatment-I, 30% as Treatment-II and 35% as Treatment-III). Fishes were fermented for 9 months by the combined action of microorganisms and enzymes present in fish tissue and viscera in presence of salt. During fermentation the initial protein content in fish was 15.17% which were nearly digested and liquefied at the end of fermentation. Crude protein content on the basis of total nitrogen were found to be 14.58, 13.88 and 12.63% in Treatment-I, II and III respectively while the highest ash content in fish sauce was 22.97% in Treatment-III. Initial Total Volatile Base Nitrogen in fish was 1.92 mg/100g, which reached 20.88, 20.52 and 20.31 mg/100g respectively in three treatments. Initial aerobic plate count (APC) in fish was 5.99 × 106 cfu/g and after fermentation and 15 days of aging the APC in fish sauce was reduced to 1.53 × 104 cfu/ml in Treatment-I, 1.40 × 104 cfu/ml in Treatment-II and 1.27 × 104 cfu/ml in treatment-III. The major bacterial groups identified in fish sauce were Bacillus, Micrococcus, Lactobacillus and Pseudomonas. Considering the values of different parameters and result of panel test, fish sauce produced with 25% salt (Treatment-I) was found to be of best quality. DOI: http://dx.doi.org/10.3329/pa.v24i1-2.19170 Progress. Agric. 24(1&2): 171 - 180, 2013